Innovative winemaking: Consumer acceptance of red table wines - Castilhos, Maurício Bonatto Machado de [UNESP]; Cattelan, Marília Gonçalves [UNESP]; Conti-Silva, Ana Carolina [UNESP]; Bianchi, Vanildo Luiz Del [UNESP] (Emerald, 2013)
Purpose: This paper aims to evaluate the consumer acceptance of Bordô and Isabel wines from innovative winemaking in order to increase red wine consumption by consumers to obtain nutritional benefits. Design/methodology/approach: All wines were produced by a standard procedure of vinification. Pre-drying treatment aimed at drying the grapes up to 22°Brix and static pomace wines presented the constant contact between the must and pomace. Sensory acceptance was carried out by 80 consumers who evaluated eight samples (six experimental wines and two commercial wines) concerning the attributes: appearance, aroma, body, flavor and overall acceptance. Findings: Experimental wines presented higher acceptance when compared to commercial wines and cluster analysis shows the splitting of consumer preferences, highlighting the higher acceptance of traditional Bordô wine and static pomace samples in all sensory attributes. Pre-drying process enhances the concentration of coloured compounds, to highlight the appearance acceptance of these samples. Research limitations/implications: Although this paper has limited the consumer acceptance of red table wines, the innovative treatments will be applied in Vitis vinifera red wines. Practical implications: The wide acceptance of static pomace and pre-drying wines has promoted further information about innovative winemaking that can be applied in Brazilian and worldwide wineries. Social implications: The innovative treatments can change sensorial features of wines and therefore influence the choice of consumers as well as enhancing the nutritional benefits of red wines. Originality/value: The pre-drying and static pomace winemaking are the novelty of this study and the wide acceptance of the sensory attributes concerning these treatments indicates the potential for application in wineries. © Emerald Group Publishing Limited.
Keywords: Cluster analysis; Consumer acceptance; Consumers; Multidimensional scaling; Red table wine; Red wines; Sensory evaluation; Wines